واقع عملية إدارة المخاطر في شركات المقاولات دراسة مسحية على شركات المقاولات العاملة في الساحل السوري - برهوم أديب (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Risk in construction industry is a real fact, and most of construction companies are working under risk and uncertainty, but in a different and varying degrees. Project risk management (PRM) plays a pivotal role in addressing and handling these various risks. Based on the above this research came mainly to study and assess the reality of risk management in the construction companies operating in Syria. We followed the descriptive study (survey) in this research based on the problem of the study and objectives it seeks to achieve. The study population included all construction companies operating in Syria. The researcher used a questionnaire specifically designed to assess risk management maturity in construction companies by (Zhao et al, 2013) & (Ciorciari & Blattner, 2007), and the questions have been adapted with the Syrian environment. The findings of this study show that there is a marked decrease in the level of maturity of the project risk management in the construction companies operating in Syria, where the maturity level is located within the first level, which does not meet the minimum requirements of the risk management process in these companies. The reason for this is the absence of risk management culture among high level management and therefore workers. This low level of maturity is a major threat because it keeps the a lot of risks unknown and therefore unknown effects and consequences. The most important recommendations reached by the student is: 1-The construction companies operating in Syria are recommended to disseminate the culture of risk management in their work environment. 2- The construction companies operating in Syria are recommended to activate the exchange of information and communication between all departments and projects, not only with high level management. يعد الخطر في صناعة المقاولات حقيقة قائمة وأغلب الشركات تتعرض له ولكن بدرجات مختلفة ومتفاوتة. تلعب إدارة مخاطر المشروعات دوراً محوريا في عملية معالجة هذه المخاطر، انطلاقاً مما سبق جاء هذا البحث بشكل أساسي بهدف دراسة وتقييم واقع عملية إدارة المخاطر في شركات المقاولات العاملة في الساحل السوري. تمَّ إتباع المنهج الوصفي في الدراسة استناداً إلى المشكلة والأهداف التي تسعى إلى تحقيقها، وشمل مجتمع الدراسة كافة شركات المقاولات العاملة في الساحل السوري. تم جمع البيانات باستخدام استبانة مصممة خصيصاً لقياس مستوى نضج إدارة المخاطر في شركات المقاولات وذلك بالاعتماد على الأداتين المطورتين من قبل (Zhao et al, 2013) و (Ciorciari & Blattner, 2007) وتمَّ تكييف الأسئلة مع البيئة في الساحل السوري. تَبَيَّنَ مِنْ خلال الدراسة بأنه يوجد انخفاض ملحوظ في مستوى نضج إدارة مخاطر المشروعات في شركات المقاولات العاملة في الساحل السوري، حيث يقع مستوى النضج ضمن المستوى الأول والذي لا يلبي أدنى احتياجات عملية إدارة المخاطر في هذه الشركات، والسبب في ذلك برأي الباحث يعود إلى غياب ثقافة إدارة المخاطر لدى الإدارات وبالتالي العاملين، الأمر الذي يعد تهديداً كبيراً لأنه يبقي القسم الأكبر من المخاطر مجهولاً وبالتالي آثاره ونتائجه مجهولة. ومن أهم التوصيات التي تمَّ التوصل إليها هي: 1- تُوصَى شركات المقاولات العاملة في الساحل السوري بضرورة نشر ثقافة إدارة المخاطر في بيئة عملها وزيادة موارد هذه الإدارة المادية والبشرية. 2- توصى شركات المقاولات العاملة في الساحل السوري بضرورة تفعيل عملية تبادل المعلومات والاتصالات بين إدارة مخاطر المشروعات وكافة إدارات ومشاريع الشركة وألا تكون علاقتها بالإدارة العليا فقط.